A clinico-neurophysiological study of urogenital dysfunction in MOG-antibody transverse myelitis. (24th November 2020) - Li, Vivien; Malladi, Prasad; Simeoni, Sara; Pakzad, Mahreen; Everett, Rosie; Satukijchai, Chanjira; Leite, Maria Isabel; Palace, Jacqueline; Panicker, Jalesh N.
Abstract : Objective: To assess the clinical, urodynamic, and neurophysiologic features of patients with persisting bladder, bowel, and sexual dysfunction after transverse myelitis in myelin oligodendrocyte glycoprotein antibody (MOG-Ab) disease. Methods: Patients with a history of MOG-Ab disease–related transverse myelitis seen prospectively in a tertiary center uro-neurology service between 2017 and 2019 were included. They received cross-sectional clinical assessment; completed standardized questionnaires on bladder, bowel, and sexual symptoms; and underwent urodynamic and pelvic neurophysiologic investigations. Results: Twelve patients (9 male) were included with a total of 17 episodes of transverse myelitis. Mean age at first attack was 26 (SD 9) years, and median follow-up duration was 50 (interquartile range 32–87) months. Acute urinary retention requiring bladder catheterization occurred in 14 episodes and was the first symptom in 10 episodes. Patients with lesions affecting the conus medullaris required catheterization for significantly longer durations than those without a conus lesion (median difference 15.5 days, p = 0.007). At follow-up, all patients had recovered full ambulatory function, but persisting bladder and bowel dysfunction moderately or severely affected quality of life in 55% and 36%, respectively, and 82% had sexual dysfunction. Pelvic neurophysiology demonstrated abnormal residual conus function in 6 patients. Urodynamic findings predominantly showed detrusor overactivity and/or detrusor-sphincter dyssynergia, indicative of a supraconal pattern of lower urinary tract dysfunction. Conclusions: Persisting urogenital and bowel dysfunction is common despite motor recovery. Although a proportion of patients had neurophysiologic evidence of residual conus abnormalities at follow-up, predominant urodyamic findings suggest that ongoing lower urinary tract dysfunction results from supraconal injury.